A droplet-based platform for high throughput screening of drug administered cells - Kasım, Müge. (Thesis (M.S.) - Bogazici University. Institute for Graduate Studies in Science and Engineering, 2019., 2019)
Droplet-based microfluidic systems move forward since 2000s having benefits compared to the conventional methods like improved sensitivity, automated and high throughput operation. This thesis involves a combined approach of the engineering and biological principles and analyses within the droplet-based microfluidic system. The performances of di↵erent microfluidic bioreactor designs were tested, and the surfactant concentration against the toxicity to cells and the flow rates were optimized. Diploid BY4743 strain with GFP tagged Rpl5 protein and haploid EY0987 strain with Nop56 protein were treated with hydroxyurea (HU) and temsirolimus drugs to understand the functions of these proteins in ribosome biogenesis. The responses of the cells were measured based on the cell area and the amount of protein expressions. SOM analysis was performed, and several clustering approaches gather the over- and underexpressed genes together. GO analysis was applied to these clusters to understand the cumulative functions of the genes in the clusters. The experimental and computational results on the response of the cells were interpreted within the context of ribosome biogenesis. HU inhibits cell growth, decreases cell dimension and protein expression of Nop56 and Rpl5, which function in ribosome biogenesis. Temsirolimus, inhibits EY0987 yeast cell growth, decreases cell dimension and protein expression of Nop56, whereas the drug e↵ects on diploid BY4743 strain and Rpl5 protein are unclear. SOM analysis reveals that the clusters, in which NOP56, NOP58 and RPL5 are involved, are related to ribosome biogenesis, rRNA processing and nucleolus, and the genes in these clusters are suppressed after 10 to 14 minutes of rapamycin treatment. This study elucidates the role of nucleolar components, snoRNP proteins, in ribosome biogenesis and confidently lead to novel therapeutic strategies for ribosomal protein related diseases.
Keywords: Nuclear liquid drop model.